Review of the evolution and prevention of friction, wear, and noise for water-lubricated bearings used in ships - Zhuo Zhang; Wu Ouyang; Xingxin Liang; Xinping Yan; Chengqin Yuan; Xincong Zhou; Zhiwei Guo; Conglin Dong; Zhenglin Liu; Yong Jin; Jinhua Xiao (Friction)
Abstract With the development of green tribology in the shipping industry, the application of water lubrication gradually replaces oil lubrication in stern bearings and thrust bearings. In terms of large-scale and high-speed ships, water-lubricated bearings with high performance are more strictly required. However, due to the lubricating medium, water-lubricated bearings have many problems such as friction, wear, vibration, noise, etc. This review focuses on the performance of marine water-lubricated bearings and their failure prevention mechanism. Furthermore, the research of marine water-lubricated bearings is reviewed by discussing its lubrication principle, test technology, friction and wear mechanism, and friction noise generation mechanism. The performance enhancement methods have been overviewed from structure optimization and material modification. Finally, the potential problems and the perspective of water-lubricated bearings are given in detail.